Penentuan Fase dan Waktu Siklus Optimum Simpang Bersinyal dengan Graf Kompatibel dan Webster Modifikasi (Studi Kasus: Persimpangan Sokaraja, Banyumas) - Dian Pratama; Kukuh Rahayu; Ambar Winarni (Mathematics Department, Faculty of Sciences and Technology Unisda Lamongan, 2025)
Traffic congestion at signalized intersections can be reduced through proper signal timing. This study aims to optimize traffic-signal settings at the Sokaraja intersection, Banyumas Regency, using a directed compatibility graph and a modified Webster method. Primary data collected from October 2025 to Desember 2025 include intersection geometry (approach widths), existing signal timings, and traffic volumes (heavy vehicles, light vehicles, and motorcycles) observed over two weeks during morning, midday, and afternoon periods. Traffic movements were modeled using a directed compatibility graph to identify non-conflicting movements that can run simultaneously; weighting based on approach width and traffic volume was then used to form phases and allocate green splits. The modified Webster calculation yields an optimal cycle length of 149 s for the maximum-demand condition (and 35 s for the minimum-demand condition). Compared with field timings (e.g., red/green 117/70 s on Jl Jendral Soedirman and 137/22 s on Jl Ajibarang–Secang), the recommended timings under maximum demand are 50/86 s and 81/54 s, respectively. Effectiveness evaluation indicates that the red intervals on Jl Jendral Soedirman and Jl Ajibarang–Secang are longer than required, while the other approaches are closer to the optimized settings. These results provide a practical basis for signal retiming and for developing more adaptive control at the Sokaraja intersection.